The Influence of the Use of Educational Game Learning Media "Snake and Ladder" on Mathematics Learning Outcomes Elementary School Students - Azizah, Fitria Kautsari; Findrayani (At-Taqaddum, 2024)
This study compares results from several sources published between 2016 and 2024. The method used is PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analysis). This research includes an analysis of the title, abstract, introduction, methodology, results, discussion, and conclusions from the included sources. The research results have an average effect size of 1.36 in the high category. The high effect size shows that using snakes and ladders learning media effectively improves mathematics learning achievement in elementary schools.